The effect of different storage times and methods on the chemical and organoleptic properties of white cooked rice and black cooked rice - Purwaningsih, Heni; Kristamtini, Kristamtini; Rahardjo, Pamudji; Nusantoro, Bangun Prajanto; Apriyati, Erni; Indrasari, Siti Dewi; Rubiyo, Rubiyo (AIMS Press, 2022)
Storage of rice for a certain period of time can lead to decrease in the quality of rice, hence the purpose of this study was to determine the effect of storage method and duration on total sugar content, starch, and preference level of Inpari 43 GSR white rice and black rice Sembada Hitam varieties. The research was conducted at the Food Biochemical Chemistry Laboratory, Faculty of Agricultural Technology, Gajah Mada University The stage of this research is to cook the rice, and the storage time in two ways inside and outside the rice cooker is 0, 9, 18, and 27 hours, respectively. Then tested for sugar content, starch and level of preference. The experimental design used was factorial randomized design with 3 replications The stage of this research is to cook the rice, and the storage time in two ways inside and outside the rice cooker is 0, 9, 18, and 27 hours, respectively. Then tested for sugar content, starch and level of preference. The experimental design used was a factorial randomized design with 3 replications, while the Sembada Hitam variety had initial sugar content of 0.019, and 0.007 when in stored in the rice cooker and 0.001 outside the rice cooker. The increase in starch content increased at 9 hours of storage in Inpari 43 GSR and Sembada Hitam varieties and a decreased at 18 and 27 hours. Based on the test of preference for color, aroma, taste and texture, panelists preferred 9 hours of storage in the rice cooker both on rice Inpari 43 GSR and Sembada Hitam because more suitable for consumption.